Fabrication, Modification, and Emerging Applications of TiO2 Nanotube Arrays by Electrochemical Synthesis: A Review - Jian-Ying Huang; Ke-Qin Zhang; Yue-Kun Lai (International Journal of Photoenergy)
Titania nanotube arrays (TNAs) as a hot nanomaterial have a unique highly ordered array structure and good mechanical and chemical stability, as well as excellent anticorrosion, biocompatible, and photocatalytic performance. It has been fabricated by a facile electrochemical anodization in electrolytes containing small amounts of fluoric ions. In combination with our research work, we review the recent progress of the new research achievements of TNAs on the preparation processes, forming mechanism, and modification. In addition, we will review the potential and significant applications in the photocatalytic degradation of pollutants, solar cells, water splitting, and other aspects. Finally, the existing problems and further prospects of this renascent and rapidly developing field are also briefly addressed and discussed.